Proceedings of the 2019 ACL Workshop BlackboxNLP: Analyzing and Interpreting Neural Networks for NLP 2019
DOI: 10.18653/v1/w19-4817
|View full text |Cite
|
Sign up to set email alerts
|

Probing Word and Sentence Embeddings for Long-distance Dependencies Effects in French and English

Abstract: The recent widespread and strong interest in RNNs has spurred detailed investigations of the distributed representations they generate and specifically if they exhibit properties similar to those characterising human languages. Results are at present inconclusive. In this paper, we extend previous work on long-distance dependencies in three ways. We manipulate word embeddings to translate them in a space that is attuned to the linguistic properties under study. We extend the work to sentence embeddings and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…While some experiments have shown that Recursive Neural Networks can learn the main descriptive properties of long-distance dependencies in English, for example the fact that they obey a uniqueness constraint (only one gap per filler) and also that they obey island constraints (Wilcox et al, 2018), work attempting to replicate finer-grained human judgments for French have failed to show a correlation with human behaviour (Merlo and Ackermann, 2018), while other work on English has found mixed results (Chowdhury and Zamparelli, 2018). Lack of correlation with human grammaticality judgments has also been found in wh-islands and object relative clauses for both French and English (Merlo, 2019). More work will be needed to establish the exact boundaries of quantitative properties in long-distance dependencies across several languages.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While some experiments have shown that Recursive Neural Networks can learn the main descriptive properties of long-distance dependencies in English, for example the fact that they obey a uniqueness constraint (only one gap per filler) and also that they obey island constraints (Wilcox et al, 2018), work attempting to replicate finer-grained human judgments for French have failed to show a correlation with human behaviour (Merlo and Ackermann, 2018), while other work on English has found mixed results (Chowdhury and Zamparelli, 2018). Lack of correlation with human grammaticality judgments has also been found in wh-islands and object relative clauses for both French and English (Merlo, 2019). More work will be needed to establish the exact boundaries of quantitative properties in long-distance dependencies across several languages.…”
Section: Resultsmentioning
confidence: 99%
“…Future work will have to extend the investigation to other features and to other constructions that have been proposed and discussed in the theory and develop more complex models of intervention similarity. Current work is investigating the morpho-syntactic feature person and models of similarity related to word embeddings (Merlo, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For example, when faced with long-distance dependencies between two feature-sharing items in a sentence (such as those found in questions, relative clauses, pronoun anaphora, and other frequent phenomena), people exhibit effects of interference if there is a third similar element in the sentence (Rizzi, 2004 ; Franck et al, 2015 ). However, this effect of similarity interference is not correlated to the similarity of words calculated statically in a vector space or even dynamically in a neural network model of processing (Merlo and Ackermann, 2018 ; Merlo, 2019 ). The general picture that emerges from all these studies is that word similarity is a rich construct of the human lexicon, and while word embedding spaces represent some fundamental properties of semantic similarity, more nuanced notions, and some grammatically-relevant aspects, may not emerge from such representations.…”
Section: Inspiration From Human Lexical Abilitiesmentioning
confidence: 99%
“…While we have not provided in this paper a direct mechanistic model of intervention, the outcome of our quantitative investigations are relevant for the increasing body of computational research that attempts to reverse engineer current neural networks models to establish the boundaries of what they can learn. These studies have concentrated on structural grammatical competence, exemplified by long-distance agreement and relative clauses and islands, phenomena that also trigger locality effects, and have demonstrated that neural networks can learn longdistance dependencies to an interesting extent (Linzen et al 2016;Wilcox et al 2018), but do not fully show intervention effects (Merlo & Ackermann 2018;Merlo 2019). The results of the current paper are relevant for this debate as they demonstrate that any discrepancies between the human results and the machine results are not due to lack of sufficient statistical signal in the data, but are morel likely to be found in properties of the learning algorithms.…”
Section: Extending the Supporting Empirical Evidencementioning
confidence: 99%